2001
DOI: 10.1097/00006254-200105000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Toxoplasmosis: A Review

Abstract: Toxoplasmosis is caused by infection with the protozoan parasite Toxoplasma gondii. In the United States, approximately 85% of women of childbearing age are susceptible to acute infection with T. gondii. Acute infections in pregnant women may cause serious health problems when the organism is transmitted to the fetus (congenital toxoplasmosis), including mental retardation, seizures, blindness, and death. An estimated 400 to 4000 cases of congenital toxoplasmosis occur in the U.S. each year. Manifestations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
257
1
41

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(300 citation statements)
references
References 61 publications
1
257
1
41
Order By: Relevance
“…In Brazil, the Southern region, where this study was conducted, has a low prevalence of toxoplasmosis among pregnant women (Nobrega & Karnikowski 2005, Figueiro-Filho et al 2007. However, there is substantial variability in the reported data, depending on chosen population, diagnostic methods used in screening, or even the different risk factors involved in disease transmission (Buffolano et al 1996, Kapperud et al 1996, Cook et al 2000, Jones et al 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the Southern region, where this study was conducted, has a low prevalence of toxoplasmosis among pregnant women (Nobrega & Karnikowski 2005, Figueiro-Filho et al 2007. However, there is substantial variability in the reported data, depending on chosen population, diagnostic methods used in screening, or even the different risk factors involved in disease transmission (Buffolano et al 1996, Kapperud et al 1996, Cook et al 2000, Jones et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Mother-to-child transmission (MTCT) rates have been found to be around 20-50% (Jones et al 2001). Several studies have suggested lower rates of foetal transmission when maternal infection took place early during gestation (Hohlfeld et al 1989, Jenum et al 1998, Dunn et al 1999, Remington et al 2005.…”
mentioning
confidence: 99%
“…In addition to causing mortality in sea otters, T. gondii is a zoonotic pathogen that infects up to one third of the human population (Hill and Dubey, 2002). Although infection is most often asymptomatic, death due to disseminated disease can occur in immunocompromised humans, and acute infection during pregnancy can result in abortion or congenital disease in the fetus (Jones et al, 2003). Sarcocystis neurona is not known to infect humans but is one of the main causes of equine protozoal myeloencephalitis (EPM), resulting in substantial morbidity and mortality of affected animals (Fenger, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of T. gondii to the fetus might result in mental retardation, seizures, blindness, hydrocephalus, cerebral calcifi cation, chorioretinitis, and ultimately death (4) . However, in some cases the health problems remain unapparent until the second or third decade of life (5) .…”
mentioning
confidence: 99%